2020
DOI: 10.3390/medicina56010025
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Treatment of Painful Diabetic Neuropathy: A Narrative Review

Abstract: Background and Objectives: Distal symmetrical polyneuropathy (DSPN) is one of the most common chronic complications of diabetes mellitus. Although it is usually characterized by progressive sensory loss, some patients may develop chronic pain. Assessment of DSPN is not difficult, but the biggest challenge is making the correct diagnosis and choosing the right treatment. The treatment of DSPN has three primary objectives: glycemic control, pathogenic mechanisms, and pain management. The aim of this brief narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 79 publications
0
26
1
5
Order By: Relevance
“…The contribution of obesity to the risk of DFU is questionable. There are studies revealing that it is associated with DFUs, while other studies show that BMI has no significant correlation [ 18 , 19 , 20 , 21 ]. The analysis revealed that patients with DFU had higher BMIs range (from 25 to 46 kg/m 2 ), and the DFU prevalence was higher in type 2 diabetes mellitus than in type 1 diabetes mellitus patients, which was consistent with the results of previous studies, but the mechanisms explaining it were not completely elucidated [ 20 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of obesity to the risk of DFU is questionable. There are studies revealing that it is associated with DFUs, while other studies show that BMI has no significant correlation [ 18 , 19 , 20 , 21 ]. The analysis revealed that patients with DFU had higher BMIs range (from 25 to 46 kg/m 2 ), and the DFU prevalence was higher in type 2 diabetes mellitus than in type 1 diabetes mellitus patients, which was consistent with the results of previous studies, but the mechanisms explaining it were not completely elucidated [ 20 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This figure is also extended to those professional figures who by definition acquire skills during the university training courses (Langher et al, 2014(Langher et al, , 2018Donsì, 2018, Settineri et al, 2018;Parola and Donsì, 2019;Merlo et al, 2020b;Parola and Felaco, 2020). The success or failure of therapies and treatments often depends on the skills of health professionals, and this suggests that they cannot be overlooked, with particular reference to adult and adolescent medical conditions (Mullen, 1997;Brown, 1999;Lingiardi et al, 2010;Shrivastava et al, 2013;Sugiharto et al, 2017;Di Giuseppe et al, 2019a;Martino et al, 2019a;Rosa et al, 2019Ardeleanu et al, 2020;Martino et al, 2020;Moroianu et al, 2020;Muzi, 2020;Nedelcu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic principles of DN may be summarised as follows: optimisation of glycaemic control, treatment of other vascular risk factors (dyslipidaemia, hypertension, smoking), pathogenesis-oriented treatment, analgesia as required and avoidance of complications (such as foot ulceration) [1,4,19]. There has been considerable progress in pain relief [1,4,19]. Conversely, pathogenesis-oriented treatment is still suboptimal and only alpha-lipoic acid has shown efficacy [4,19].…”
Section: Dnmentioning
confidence: 99%
“…There has been considerable progress in pain relief [1,4,19]. Conversely, pathogenesis-oriented treatment is still suboptimal and only alpha-lipoic acid has shown efficacy [4,19].…”
Section: Dnmentioning
confidence: 99%